Pengembangan Lembar Kerja Siswa untuk Memfasilitasi Pencapaian Penguasaan Konsep Matematika - Efuansyah Efuansyah; Reny Wahyuni (Numerical: Jurnal Matematika dan Pendidikan Matematika)
This research aims to develop worksheets to facilitate the ability to understand mathematical concepts in the material of one-variable linear equations, to determine the quality of worksheets developed in terms of validity and practicality, and to understand the ability to understand mathematical concepts after the use of LKS in one variable. The subjects were seventh grade students of Lubuklinggau 7th Junior High School. A development research that refers to the 4-D development model. In the Design phase includes: preparation of instruments consisting of validity LKS sheet, practicality assessment sheet LKS and test instruments for understanding mathematical concepts. Furthermore, the format selection consists of compiling the framework and systematic preparation of LKS, so that the prototype LKS is formed 1. Develop phase, the LKS is validated by mathematicians and experts, suggestions and comments from the validator are used as references in revising the LKS, thus producing a prototype 2. Next is LKS was tested in a small group and produced a prototype 3, then tested on a large group. The last stage is Disseminate, LKS products are distributed to class VII math teachers, principals, and grade VIII mathematics teachers. The quality of LKS developed based on the validity aspects is in the Good category with an average score of 4.0, while the quality of the LKS from the practical aspect is in the Excellent category with an average score of 0.84. In the test the ability to understand mathematical concepts is in the Good category with an average value of 80,966